1989
DOI: 10.1515/botm.1989.32.6.527
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase in Gracilaria secundata (Rhodophyta) and its Role as a Nitrogen Storage Pool

Abstract: The large subunit of ribulose-l,5-bisphosphatecarboxylase/oxygenase (RuBPCase, EC 4.1.1.39) in Gracilaria secundata Harv. was localized, by use of immuno-gold labelling technique and transmission electron microscopy, to chloroplasts and crystalline inclusions. Changes in amounts of the RuBPCase large subunit were observed and followed during a nitrogen starvation experiment with the seaweed. These changes are discussed in relation to changes in nitrogen content of the alga.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Thus, PBP could act as a N reserve in the context of a more general response of chloroplast proteins to N limitation. In agreement with this hypothesis, the selective response of the enzyme nbulose-1,5-biphosphate carboxylase/oxygenase (Rubisco) to N availability has been shown in microalgae (Falkowski et al 1989, Geider et al 1994) and in red algae (Lapointe & Duke 1984, Ekman et al 1989, Garcia-Sanchez et al 1993, where both Rubisco subunits are chloroplast-encoded proteins (Valentin & Zetsche 1989). This attractive hypothesis, proposed by Falkowski et al (1989), merits closer examination, and further investigation is need to elucidate the existence of such a mechanism in red algae.…”
Section: Differential Protein Synthesismentioning
confidence: 81%
“…Thus, PBP could act as a N reserve in the context of a more general response of chloroplast proteins to N limitation. In agreement with this hypothesis, the selective response of the enzyme nbulose-1,5-biphosphate carboxylase/oxygenase (Rubisco) to N availability has been shown in microalgae (Falkowski et al 1989, Geider et al 1994) and in red algae (Lapointe & Duke 1984, Ekman et al 1989, Garcia-Sanchez et al 1993, where both Rubisco subunits are chloroplast-encoded proteins (Valentin & Zetsche 1989). This attractive hypothesis, proposed by Falkowski et al (1989), merits closer examination, and further investigation is need to elucidate the existence of such a mechanism in red algae.…”
Section: Differential Protein Synthesismentioning
confidence: 81%
“…However, these observations are based on studies with crude enzyme extracts and no detailed studies on puri®ed starch synthase preparations from red algae are available. Here we present the results of an investigation on starch synthase activity in the red alga Gracilaria tenuistipitata which, under certain growth conditions, can accumulate starch granules accounting for over 80% of the cell volume (Ekman et al 1989). We have found that UDPGlc is a considerably more eective glucosyl donor for starch synthase activity than ADPGlc in crude algal extracts.…”
Section: Introductionmentioning
confidence: 89%
“…an optimisation of N sources during submersion (Thomas et al 1987a). Alternatively, N storage may occur as N compounds such as amino acids, proteins, chlorophyll and accessory pigments (Gagné et al 1982, Ekman et al 1989, Fredriksen & Rueness 1989, Naldi & Wheeler 1999) rather than as soluble vacuolar/cytoplasmic NO 3 -. The ability of macroalgae to store N as a variety of compounds suggests that total N may be a better indicator of N status.…”
Section: N Status Of Intertidal Algaementioning
confidence: 99%